THE ROLE AND IMPORTANCE OF INTERNATIONAL STANDARDS IN ENSURING THE QUALITY AND SAFETY OF FOOD PRODUCTS - Najmiddin, Muminov; Elyorbek, Bakiev (PT. Antis International Publisher, 2024)
Objective: This study investigates the adoption of international agricultural standards, particularly the GLOBALGAP standard, to enhance the quality, safety, and competitiveness of Uzbekistan's agricultural products. The aim is to develop strategies for integrating these standards into the national context, thereby improving market access and economic growth. Methods: A multi-faceted approach was adopted, including data analysis of international and national agricultural standards, stakeholder engagement through interviews and focus groups, training workshops with global experts, pilot implementations on selected farms, and the development of an actionable implementation framework. Results: The implementation of GLOBALGAP standards in Uzbekistan has the potential to significantly enhance agricultural product quality and safety, increase export opportunities, and boost stakeholder confidence. Pilot projects demonstrated improved compliance with global standards, increased marketability, and readiness for wider adoption. Key challenges identified include capacity building and regulatory alignment, which were addressed through targeted training and stakeholder collaboration. Novelty: This study provides a comprehensive framework for integrating GLOBALGAP standards into Uzbekistan’s agricultural sector, tailored to its unique environmental, legislative, and market conditions. The focus on pilot implementations and collaborative approaches offers actionable insights for other countries seeking similar advancements in agricultural certification and market competitiveness.